Characterization of wollastonite-based glass ceramic from clamshell and sodium lime silica bottles - Mahmoud, Fatema Radeef (2019)
Wollastonite glass-ceramics have been fabricated in this work using clamshell (CS) and soda lime silicate (SLS) glass waste. The samples were prepared using a meltquenching technique based on the chemical formula [(CS)x(SLS)100-x] with x = 10, 20, 30, 40, and 50. The samples were sintered at 600, 700 and 1000°C.The literature has not reported the utilization of CS and the SLS glass waste in the fabrication of wollastonite based glass ceramics. The CS is chosen as a source of CaO and the SLS glass waste provides the required SiO2, and these wastes are expected to provide another alternative means of managing the disposed of SLS glass and CS wastes in the metropolitan cities around the world. Hence, the objectives of this research were to fabricate a series of wollastonite glass-ceramics from clamshell and SLS glass waste and to study both the clamshell concentration and sintering temperature effects on the physical and structural properties of the materials. To achieve the research objectives, measurements and characterizations such as density, linear shrinkage, X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), and energy dispersion X-ray fluorescence (EDX) analysis of the prepared samples were carried out. The density values and linear shrinkage mostly increased with the concentration of CS in the materials and sintering temperature where the density is 28.4 g/cm3 and the linear is 7.11 mm. This increment is probably associated with structural changes leading to more interstitial space as shown by SEM micrograph structures. The XRD results showed the presence of peaks of wollastonite, cristobalite, augite, diopside and quartz phases. The XR results show that after the sintering at 600°C, the sample was still in the amorphous phase, the increased in the sintering temperature to 700°C the peaks were found through increasing the sintering temperature to 1000°C the phase appeared. The wollastonite intensity increases when sintering temperature increases. The elemental EDX analysis of the green and sintered samples at 600°C, 700°C and 1000°C revealed the presence of carbon (C), oxygen (O), sodium (Na), silicon (Si) and calcium (Ca). The FTIR analysis of the samples showed mainly the absorptions due to the vibrations of Si–O–Si linkages, symmetric Si–O and bond bending of Si–O–Si, symmetric stretching vibrations of O–Si–O bending, and Ca–O stretching modes. The sintering temperature and clamshell concentration both have structural and physical effects on the material as revealed in FTIR spectra, that was clear when they obtained the bond of calcium groups and the bond of silicon groups.